The Foundation directory. - Foundation Center; Foundation Library Center; Russell Sage Foundation (New York Foundation Center, 1997)
Annual, 1989-
Irregular, 1960-88
Complemented by: Foundation directory. Part 2, a guide to grant programs.
Has supplement, 1988- : Directory of new and emerging foundations.
Kept up to date between editions by supplements.
Published 1960-67 by Russell Sage Foundation.
Vols. for 1960-67 prepared by the Foundation Library Center; 1971- by Foundation Center.
Keywords: Endowments -- Directories. -- United States; Foundations -- Directories; Foundations -- Periodicals